Sex bias in the serotonin transporter knockout model: Implications for neuropsychiatric disorder research. (March 2022) - Thorne, Bryony N.; Ellenbroek, Bart A.; Day, Darren J.
Highlights: Sex bias in studies of the SERT knockout model has progressively worsened since 2000. In 2016–2020, more SERT knockout publications than ever exclusively studied male animals. Studies of the SERT knockout model lag neuroscience research for addressing sex as a biological variable. Abstract: Serotonergic signalling is implicated in the aetiology of many neuropsychiatric disorders. The serotonin reuptake transporter (SERT) is an important regulator of synaptic serotonin, being an important pharmacological target with genetic variants implicated with risk of developing neuropsychiatric disorders. Animal models have played an important role in understanding the genetic risk and role of SERT function in brain development having highlighted sex differences in incidence, presentation, and treatment efficacy, however, sex bias due to unequal representation of sexes in research remains a significant issue. While more studies are addressing sex as a biological variable this is not reflected in studies using SERT knockout models as the proportion including sex comparisons has declined since 2000. This bias needs to be addressed if research findings from animal studies are to have translation relevance to human conditions.